The Sources of Tourism Financing in Nepal an Assessment (Socio-Economic Development Panorama, 2008)
Finance of the tourism sector smoothly requires several sources to be tapped. Among them blending in of private investment, government investment, and foreign investment are some vital tools. However, during the review period covered, the role of the government appeared to be quite limited leaving the overall tourism industry operation heavily reliant upon the private sector hands. However, the government policy is positive towards the overall development of tourism industry. The government thus introduced investment promotion incentives, formulated an investment legislation, and regulated the tourism sector, accordingly. This study points out to the pitfalls on the tourism sector and points out to the dire consequences of how investment of only a meager amount of budget allocation by the government. Likewise, mobilization of foreign aid and loan assistance on the overall economic sector is on the increase dampening entrepreneurship. Foreign Direct Investment (FDI) in tourism sector also has been greatly hit in a similar fashion. Despite this phenomenon, tourism sector has been able to be greatly enjoying private sector investment enriched with generous lending facilities initiated by the banks and financial institutions. Over the years, financing has reached to its zenith heights. However, tourism industry has a long way to go to dramatically usher into an unprecedented growth. Tourism, if harnessed properly has all the ingredients to become a potential backbone economic growth sector of Nepal. Keywords: Tourism, financing of tourism, government and tourism, loan, assistance banks and tourism, lending, foreign direct investment, financial resources Socio Economic Development Panorama, Vol. 1, No.3(2008) pp. 79-96